The human-feline relationship from a biocultural perspective: perception, knowledge and traditional use of the six Mexican species, in the state of Hidalgo, Mexico - Valencia-Herverth, Jorge; Gutiérrez Santillán, Tania Vianney; Valencia-Herverth, Raúl; Estrada-Castillón, Eduardo (Ethnobiology and Conservation, 2025)
The human-feline relationship has been evaluated mainly from the perspective of conservation biology. However, it is important to know the established socioecological relationships, unfortunately, little explored, despite the documentation and importance of these predators. In this study, the perceptions and knowledge were documented, as well as the evaluation of the cultural roles of use carried out by the Nahua inhabitants of the north-eastern region of the state of Hidalgo, Mexico; towards the six species of wild cats. 150 semi-structured interviews were applied and photographs were taken of the evidence of felines or their parts in the possession of the informants. Wild felines are identified with a name in Nahuatl and in Spanish. The species that presented the highest frequency of mention, as well as value of cultural importance, was the ocelot (margay, Leopardus wiedii). Nine categories of use were identified, with ornamental use being the most relevant. In addition, we documented the consumption of lion meat (cougar, Puma concolor) as a complex socio-ecological phenomenon, derived from retaliation. As well as the hunt for a tiger cub (jaguar, Panthera onca), captured in a playful way, despite manifesting full knowledge that it is an endangered species, protected by Mexican legislation and its hunting is illegal. Wild cats, despite their decline due to anthropocentric causes, continue to play a relevant socio-ecological role and are part of the biocultural diversity of indigenous peoples. Unfortunately, negative perceptions and overvaluation of species indirectly encourage illegal hunting or extraction.